Institutional environment and determinants of adjustment speed to the target capital structure in the MENA region - Marwa Touil (Borsa Istanbul Review, 2020)
We investigate financial structure institutional determinants of firms listed on the MENA region, and we analyze the indirect role played by institutions on the speed of adjustment. We consider a sample of 506 non-financial firms from 12 MENA countries listed on the stock exchange between 2006 and 2014. We find that the effects of firm profitability, non-debt tax savings and growth opportunities on leverage are strengthened in the context of good quality institutions. In the contrast, the effects of firm size and returns volatility are reduced. Regarding the adjustment speed, we find that the financial market development and the good quality of institutions tend to reinforce the effects of firm profitability and distance from the target. However, they moderate the influence of firm returns volatility, growth opportunities, non-debt tax savings, and asset tangibility on the adjustment process. We also note that political stability plays an indirect role to control bankruptcy costs and information asymmetries. Our results have important implications since they can interest firm executives and investors in MENA countries, and more generally in developing countries. They may provide answers to questions about the role played by institutions in the adjusting process to the target debt ratio.